Update on clinical research for food allergy treatment - Fowler, Joshua; Lieberman, Jay (Frontiers in Allergy, 2023)
The incidence of IgE-mediated food allergy (FA) has continued to increase over the years which places substantial burden on patient health and quality of life. With no cure for this disease, the mainstay of management has been allergen avoidance. However, there have been advancements in FA treatment in recent years with multiple clinical trials utilizing novel and innovative therapeutic strategies. A landmark event came in 2020 with the first drug approval for food allergy with the approval of a product for peanut oral immunotherapy. In addition to oral immunotherapy, different delivery systems of immunotherapy (SLIT, EPIT) are being studied in addition to probiotics, biologic agents - used as monotherapy and as an adjunct, and modified allergens has taken place with the hope to further enhance existing therapeutic options. The hope through these continued developments is for therapies to emerge that will provide a more comprehensive benefit to this patient population.